Improving medical certification of cause of death in Assiut University Children Hospital: an intervention study - Omaima El-Gibaly; Mohamed Gamil Mohamed Abo Elela; Yasser Farouk Abdel-Raheem Rizk; Shimaa Hosny Hassan Mahmoud (BMC, 2024)
Abstract Introduction Death certification is a health indicator and a public health surveillance tool. High-quality death certificate ensures reliability of mortality statistics used to direct the arranging of health-related programs and leading assessments of research and proper healthcare outcomes. The World Health Organization (WHO) puts Egypt in the group of 'low quality' death registration data. The aim of this study was to evaluate the impact of composite training and audit intervention on accurate completion of death notification forms (DNFs) in Assiut University Children Hospital (AUCH) that has an average monthly mortality of 120 children's deaths. Methods A Quasi-experimental study design was conducted among residents of AUCH. The intervention consisted of 1- Preparing training material with basic information on how to report causes of death according to WHO criteria and case scenarios extracted from the medical records of children who died at AUCH, 2- One hundred residents of the AUCH were trained in one day workshops in 4 groups, with a pre-post knowledge assessment questionnaire. 3- A weekly audit of a sample of 10-15 DNFs was done for six months with reporting of findings to quality assurance director of the hospital. Results Eighty- nine physicians completed the pre-post knowledge assessment with significant increase in knowledge score after the intervention (15.7 ± 3.2 vs. 11.9 ± 2.8). There was a significant decrease in the errors of reporting on the DNFs. The main improvement was in decrease from 90 to 18% in reporting the mechanism of death, and significant decline in writing cause of death in Arabic language only. Conclusion Accurate reporting of the medical cause of death can be achieved by educational intervention targeting physicians with institutionalizing of audit system for continuous quality improvement.